2012
DOI: 10.3233/wor-2012-0491-2510
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for repetitive strain injuries among school teachers in Thailand

Abstract: Prolonged posture, static works and repetition are previously reported as the cause of repetitive strain injuries (RSIs) among workers including teachers. This cross-sectional analytic study aimed to investigate the prevalence and risk factors of RSIs among school teachers. Participants were 452 full-time school teachers in Thailand. Data were collected by the structural questionnaires, illuminance measurements and the physical fitness tests. Descriptive statistics and inferential statistics which were Chi-squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 9 publications
(10 reference statements)
0
29
0
2
Order By: Relevance
“…Chaiklieng and Suggaravetsiri 35 found a significant association between use of high heels and repetitive strain injury in teachers (OR=1.60). Keegan et al 37 profiled footwear worn at time of fall by participants who fractured and those who did not and found that medium-to-high heel height was associated with increased risk of fracture of the foot (OR=2.0), distal forearm (OR=1.7), proximal humerus (OR=1.5), pelvis (OR=1.5) and shaft of the tibia/fibula (OR=1.7).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Chaiklieng and Suggaravetsiri 35 found a significant association between use of high heels and repetitive strain injury in teachers (OR=1.60). Keegan et al 37 profiled footwear worn at time of fall by participants who fractured and those who did not and found that medium-to-high heel height was associated with increased risk of fracture of the foot (OR=2.0), distal forearm (OR=1.7), proximal humerus (OR=1.5), pelvis (OR=1.5) and shaft of the tibia/fibula (OR=1.7).…”
Section: Resultsmentioning
confidence: 98%
“…Eight studies assessed the association between high heels and first-party injury, of which seven 18 35–40 (88%) were positive and one 41 (12%) was negative. Of the positive studies, five 18 35 37 38 40 were assessed as high quality and two 36 39 as moderate quality. The only negative study was assessed as moderate quality.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies also highlight the high frequency of self-medication in cases of headache 11,14 . Regarding chronic pain in the upper and lower limbs, inadequate working postures and conditions are frequently associated with its onset and perpetuation 15,16 . As long as the working conditions are not goodness-of-fit, teachers will look for adaptations in an attempt to guarantee the quality of life and work.…”
Section: Discussionmentioning
confidence: 99%
“…Among workers including teachers, prolonged posture, static work and repetition are the cause of repetitive strain injuries (RSIs), which is one type of MSD that directly affects the area of upper limb, neck, shoulder and low back [22]. Smith et al, 1997 showed that compared to a control group, teachers were significantly more likely to report having 6 voice symptoms, among which hoarseness was the most frequent, and 5 related physical discomfort symptoms (tiring, effortful, ache, uncomfortable and rough) [23,24].…”
Section: Discussionmentioning
confidence: 99%